Impact of Non-Persistence on Healthcare Resource Utilization and Costs in Patients With Immune-Mediated Rheumatic Diseases Initiating Subcutaneous TNF-Alpha Inhibitors: A Before-and-After Study - Carballo, Nuria; Garcia-Alzórriz, Enric; Ferrández, Olivia; Navarrete-Rouco, María Eugenia; Durán-Jordà, Xavier; Pérez-García, Carolina; Monfort, Jordi; Cots, Francesc; Grau, Santiago (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis are chronic progressive immune-mediated rheumatic diseases (IMRD) that can cause a progressive disability and joint deformation and thus can impact in healthcare resource utilization (HCRU) and costs. The main outcome of the study was to assess the effect of non-persistence to treatment with subcutaneous tumor necrosis factor-alpha inhibitors (SC-TNFis) on HCRU costs in naïve patients with IMRD who started treatment with adalimumab, etanercept, golimumab or certolizumab pegol during 12 months after initiation of treatment. The impact of persistence and non-persistence of SC-TNFis on HCRU costs was compared between 12 months before and 12 months after initiating SC-TNFis. Persistence was defined as the duration of time from initiation to discontinuation of therapy. The study was conducted in an acute care teaching hospital in Barcelona, Spain. Data for the period between 2015 and 2018 were extracted from the hospital cost management control database. HCRU costs comprised outpatient care, outpatient specialized rheumatology care, in-patient care, emergency care, laboratory testing and other non-biological therapies. The study population included 110 naïve SC-TNFis patients, divided into the cohorts of persistent (n = 85) and non-persistent (n = 25) patients. Fifty-six percent of patients were women, with a mean (standard deviation) age of 47.6 (14.8) years. Baseline clinical features and HCRU costs over the 12 months before the index prescription were similar in the two study groups. Before-and-after differences in mean (standard deviation) HCRU costs were significantly higher in the non-persistence group as compared to the persistence group for outpatient rheumatology care (€110.90 [234.56] vs. €20.80 [129.59], P = 0.023), laboratory testing (-€193.99 [195.88] vs. -€241.3 [217.88], P = 0.025), other non-biological drugs (€3849.03 [4046.14] vs. -€10.90 [157.42], P < 0.001) and total costs (€3268.90 [4821.55] vs. -€334.67 (905.44), P < 0.001). Treatment persistence with SC-TNFis may be associated with HCRU cost savings in naïve IMRD patients. Prescribing SC-TNFis with the best long-term persistence is beneficial.